Aplikasi Ekstrak Mimosa invisa L. dan Pupuk NPK Dosis Rendah dalam Pengendalian Hama dan Patogen Padi Gogo - Yugi Rahayu Ahadiyat; Heru Adi Djatmiko; Risqa Naila Khusna Syarifah (Institut Pertanian Bogor, 2024)
This study aimed to determine the effect of Mimosa invisa L. weed extract application and a low dose of NPK fertilizer on the intensity of pest attack and pathogen infection on upland rice. This research has been done using Split Plot Design with 3 replications. The main plot was the dose of NPK fertilizer (50% and 100% NPK). The subplot was the concentration of weed extract (0, 1.25, 1.67, 2.5, and 5% concentrations). The variables observed include the intensity of grasshopper and case worm attack, Cercospora sp. that causes brown spots, and Xanthomonas oryzae pv. oryzae that causes bacterial leaf blight. The results showed that the application of weed extract under a low dose (50% NPK) has not been able to suppress the intensity of grasshopper and case worm attacks, and the intensity of the pathogen causes brown spots and bacterial leaf blight. However, 2,5% and 5% concentrations of weed extract can potentially suppress pathogen infection that causes brown spots on upland rice. Keywords: grasshopper, brown spots, Mimosa invisa L.weed extract, case worm, bacterial leaf blight, NPK fertilizer